2007
DOI: 10.1128/aem.02750-06
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Interpretation of Bacterial Viability by Using the LIVE/DEAD BacLight Kit in Combination with Flow Cytometry

Abstract: The commercially available LIVE/DEAD BacLight kit is enjoying increased popularity among researchers in various fields of microbiology. Its use in combination with flow cytometry brought up new questions about how to interpret LIVE/DEAD staining results. Intermediate states, normally difficult to detect with epifluorescence microscopy, are a common phenomenon when the assay is used in flow cytometry and still lack rationale. It is shown here that the application of propidium iodide in combination with a green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
588
2
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 762 publications
(624 citation statements)
references
References 35 publications
19
588
2
6
Order By: Relevance
“…Previous studies that used FCM analysis of SYTO/PI labeled bacteria showed that not only intact (SYTO 9 positive) and damaged cells (PI positive) are observed, but that double-stained cells (SYTO 9/PI) are also detected [26][27][28][29]. For results, SYTO 9 positive cells were referred to as "live", PI positive cells as "dead", and cells displaying a double positive signal (SYTO 9/PI) were designated "injured".…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Previous studies that used FCM analysis of SYTO/PI labeled bacteria showed that not only intact (SYTO 9 positive) and damaged cells (PI positive) are observed, but that double-stained cells (SYTO 9/PI) are also detected [26][27][28][29]. For results, SYTO 9 positive cells were referred to as "live", PI positive cells as "dead", and cells displaying a double positive signal (SYTO 9/PI) were designated "injured".…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…The reliability of the determination of the total bacterial counts by plate culture has been questioned as it is a retrospective method of bacterial viability (Berney et al, 2007) and its reproducibility is affected by factors such as transport and culture media, temperature, atmosphere and incubation period (Lehtinen et al, 2004). These problems can potentially lead to an underestimation of the total bacterial counts or overestimation in very rare cases.…”
Section: Vitromentioning
confidence: 99%
“…Since norB expression was increased shortly after a shift to pH 4.5, we wished to determine whether susceptibility to moxifloxacin, a NorB substrate (24), was also affected by a shift to pH 4.5. Cell viability was measured in response to moxifloxacin at 30 min after a shift to pH 4.5 or pH 7.0, using rapid LIVE/DEAD cell staining with a Fishman-R cytometer (4). At 90 min after addition of moxifloxacin, there was an approximately 6-fold-greater reduction of live FIG.…”
Section: Effect Of Acid Ph On Growthmentioning
confidence: 99%